Legal Antinomy in Exercising Civil Rights of Persons with Disabilities in Notarial Activities: Lessons Learned from Indonesia - Sendrawan, Tjhong; Agustina, Rosa; Makarim, Edmon (University of Jember, 2024)
This paper addresses the legal antinomy present in the exercise of civil rights for persons with disabilities (PWD) in notarial activities in Indonesia. The conflict arises between the need for legal certainty, as required by national laws, and the obligation to provide equal justice and access for PWD, as mandated by the Convention on the Rights of Persons with Disabilities (CRPD). Key provisions of the Indonesian Notary Law, particularly the Notary Law Amendment of 2014, impose barriers that hinder PWD from fully exercising their civil rights. These issues highlight the lack of clear guidelines for notaries in accommodating PWD, resulting in legal uncertainty and potential discrimination. This paper proposes legal reforms and emphasizes the need for notaries to act as facilitators of justice, ensuring equal access to civil rights for PWD in line with international human rights standards. The study employs a doctrinal legal research method, conducting literature reviews of various primary, secondary, and tertiary legal materials, such as an international convention, notary laws, books, journals, dictionaries, and research papers published relevant to the topic. This article limits the analysis of human rights of PWD to their access of civil rights services provided by a notary. A notary needs to understand and carefully make legal judgment when providing advice and drawing up notarial acts under various circumstances involving disabilities. In the end, this paper acknowledges a significant finding that Article 16 paragraph (1) letter (c), Article 42 paragraph (2) and paragraph (3), and Article 43 paragraph (3) of the Notary Law Amendment of 2014 currently hinder the exercise of civil rights of PWD. This paper offers both theoretical and empirical contributions to the ongoing discussion and presents perspectives from the Indonesian Constitutional Court Judgement Number 93/PUU-XX/2022, which amends the provisions of Article 433 Indonesian Civil Code and argues for the importance of a specific understanding and guidelines on this issue. Keywords: Access to Justice, Disability Rights, Equality, Human Rights Model, Notary Acts